STRAIN SELECTION AND CULTIVATION OF FOOT-AND-MOUTH DISEASE VIRUSES FOR THE DEVELOPMENT OF A TRIVALENT INACTIVATED VACCINE - Burashev , Y.D.; Orynbayev , М.B.; Abeuov , K.B.; Sultankulova , К.T.; Tulendibayev , А.B.; Оmarova , Z.D.; Argimbayeva , Т.U.; Yermekbai , Т.Т.; Aubakir , N.А. (Eurasian Journal of Applied Biotechnology, 2024)
Foot-and-mouth disease is a well-known transboundary animal disease and has been recognised as a priority disease by the Steering Committee of the Global Framework for the Progressive Control of Transboundary Animal Diseases in Europe. The territory of the Republic of Kazakhstan is generally free of foot-and-mouth disease, however, sporadic cases of foot-and-mouth disease occur in various regions of the country as a result of importation from unfavorable countries. Epizootic safety in the Republic of Kazakhstan is maintained by vaccinating animals in the border areas of the southern and eastern regions. Inactivated vaccines against serotypes A, O, Asia produced by the All-Russian Research Institute of Animal Health (Russia) are used for vaccination. Continuous seromonitoring is carried out to maintain the level of post-vaccination antibodies at a high level, ensuring the immunity of animals to foot-and-mouth disease. However, despite all the measures taken, sporadic outbreaks of foot-and-mouth disease cause damage to livestock farming in the Republic of Kazakhstan. The effectiveness of preventive measures using vaccination depends on the strain used in the vaccine. The closer the strain used in the vaccine is genetically to the viruses circulating in that area, the more effective the preventive measures will be and the research conducted to create the most immunogenic domestic anti-foot-and-mouth disease vaccines have scientific and practical significance. This article presents the results of the selection of foot-and-mouth disease virus strains previously circulating in the territory of the Republic of Kazakhstan and studies their cultural and biological properties. Studies of the above-mentioned strains on adaptation to a transplantable cell culture line were conducted, the stability of cultural properties was studied over 10 generations and the stability was confirmed by the PCR method. Also, based on the studies, it was found that the maximum accumulation of the virus in cell culture occurs at a multiplicity of infection of 0.01-0.1 TCID50/cell. The reproductive activity of the studied isolates was within 6.5-7.25 lg TCID50/cm3 when cultivated for 16 hours.